The Atlantic Multidecadal Variability phase-dependence of teleconnection between the North Atlantic Oscillation in February and the Tibetan Plateau in March - Li, Jingyi; Li, Fei; He, Shengping; Wang, Huijun; Orsolini, Yvan J. (Journal of Climate, 2021)
acceptedVersion